Clinical phenotypes of multisystem inflammatory syndrome in children (MIS-C) associated with COVID-19 - Alvarado-Gamarra, Giancarlo (2022)
The multisystem inflammatory syndrome in children associated with COVID-19 (MIS-C) is infre-quent but potentially lethal. There are few reports of this disease and its phenotypes in Latin America. Objective: To describe the characteristics of the clinical phenotypes of MIS-C in hospitalized patients in Lima, Peru. Patients and Method: A descriptive and retrospective study in patients under 14 years old with a diagnosis of MIS-C at the Hospital Nacional Edgardo Rebagliati Martins (Lima, Perú), from April 2020 to August 2021. Clinical-demographic and microbiological variables were recorded. According to these, patients with MIS-C were classified into the shock phenotype, Kawasaki disease (KD) without shock, and the fever and inflammation phenotype, analyzing their clinical outcomes. Results: 58 patients were analyzed. 32 (55.2%) presented the shock phenotype, 15 (25.8%) Kawasaki disease (KD) phenotype without shock, and 11 (19%) fever and inflammation phenotype. In the shock phenotype, 17 had KD. The mean age was 7 ± 3.5 years and 67.2% were males. Gastrointes-tinal and mucocutaneous manifestations predominated in all phenotypes. The mortality was 3.5%. The frequency of coronary aneurysms was 10.2%. Most patients received immunomodulatory and antiplatelet treatment. Patients with shock phenotype showed greater involvement in inflammatory markers, hematological dysfunction, and myocardial injury, with a higher frequency of respiratory failure and invasive mechanical ventilation. Conclusions: In our case series, patients with shock phenotype were the most frequent and had worse clinical outcomes. Active surveillance of clinical phenotypes is needed to make an early diagnosis and management to improve the prognosis in these patients.